Preparation method of amorphous basic cupric carbonate

By reacting soluble copper salts with an alkaline precipitant, adding the stabilizer isopropylamine chain dodecylbenzene sulfonate, and performing low-temperature washing and freeze-drying treatment, the problem of preparing amorphous basic copper carbonate was solved, and the preparation of stable amorphous basic copper carbonate was achieved.

CN121202176APending Publication Date: 2025-12-26CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410814947.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

Existing technologies make it difficult to prepare stable amorphous basic copper carbonate, and conventional methods are prone to causing crystal structure transformations, making it difficult to obtain pure amorphous basic copper carbonate samples.

Method used

Amorphous basic copper carbonate was prepared by reacting a soluble copper salt with an alkaline precipitant, adding the stabilizer isopropylamine chain dodecylbenzene sulfonate, and combining it with low-temperature washing and freeze-drying to avoid crystal transformation.

Benefits of technology

Stable amorphous basic copper carbonate was successfully prepared, avoiding crystal transformation. The method is simple and easy to operate, and does not require expensive instruments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121202176A_ABST
    Figure CN121202176A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of amorphous basic cupric carbonate. The method comprises the following steps: (1) respectively preparing a soluble copper salt solution and a precipitant solution; (2) adding bottom water and a stabilizer into a reactor, adding the soluble copper salt solution and the precipitant solution obtained in the step (1) into the reactor in a parallel flow manner, and reacting while stirring to obtain slurry; the stabilizer is a solution containing isopropylamine chain dodecyl benzene sulfonate; (3) carrying out suction filtration and first washing on the slurry obtained in the step (2); (4) adding the material obtained in the step (3) into a solvent, and freezing; and (5) sequentially carrying out second washing, third washing and fourth washing on the material obtained in the step (4), and carrying out freeze drying on the washed material to obtain the amorphous basic cupric carbonate. According to the method, crystal structure transformation of amorphous basic cupric carbonate in the preparation process can be avoided, and the method is simple and easy to operate and does not need expensive instruments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing amorphous basic copper carbonate. Background Technology

[0002] Basic copper carbonate [Cu₂(OH)₂CO₃], also known as malachite or verdigris, is often used in the development and production of catalysts with basic copper carbonate as the main component. This often requires the extraction of amorphous basic copper carbonate samples that have not undergone crystal transformation for further characterization and research. However, amorphous basic copper carbonate has poor stability and spontaneously undergoes a crystal transformation in air, making it difficult to obtain pure amorphous basic copper carbonate samples. Currently, there are no publicly reported methods for preparing amorphous basic copper carbonate samples before crystal transformation.

[0003] Existing technologies for preparing basic copper carbonate mainly employ precipitation methods, typically using soluble copper salts and soluble carbonates. For example, copper salt solutions such as copper nitrate or copper sulfate are used with alkaline precipitants such as sodium carbonate to induce a precipitation reaction, producing basic copper carbonate. In addition, there is the carbon dioxide method; for instance, CN111132932A discloses a method for preparing basic copper carbonate by passing carbon dioxide into copper hydroxide.

[0004] The basic copper carbonates prepared by the above conventional methods are all blue-green to dark green basic copper carbonates with a crystalline structure. None of the currently disclosed preparation methods involve how to obtain light blue amorphous basic copper carbonate solids. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing amorphous basic copper carbonate. This method avoids crystal structure transformation during the preparation of amorphous basic copper carbonate, and it is simple to operate and requires no expensive equipment.

[0006] This invention provides a method for preparing amorphous basic copper carbonate, comprising:

[0007] (1) Prepare soluble copper salt solution and precipitant solution separately;

[0008] (2) Add bottom water and stabilizer to the reactor, and add the soluble copper salt solution and precipitant solution obtained in step (1) to the reactor in parallel flow. React under stirring to obtain a slurry; the stabilizer is a solution containing isopropylamine chain dodecylbenzene sulfonate.

[0009] (3) The slurry obtained in step (2) is filtered and washed for the first time;

[0010] (4) Add the material obtained in step (3) to the solvent and freeze;

[0011] (5) The material from step (4) is washed in sequence, followed by a second, third and fourth washes. The washed material is then freeze-dried to obtain amorphous basic copper carbonate.

[0012] Further, in step (1), the soluble copper salt solution is an aqueous solution of a soluble copper salt, preferably at least one of Cu(NO3)2 solution, CuSO4 solution, CuCl2 solution, etc. The concentration of the soluble copper salt solution is 0.1–5 mol / L.

[0013] Further, in step (1), the precipitant solution is at least one of alkaline solutions such as Na2CO3 solution, NaOH solution, and NaHCO3 solution. The concentration of the precipitant solution is 0.1–5 mol / L.

[0014] Furthermore, in step (2), the amount of bottom water added is 5% to 20% of the total volume of solution finally added to the reactor.

[0015] Further, in step (2), the amount of stabilizer added is 0.5wt% to 1.5wt% of the mass of the bottom water.

[0016] Further, in step (2), based on the mass of the stabilizer, the mass content of isopropylamine chain dodecylbenzene sulfonate is 10wt% to 90wt%, with the remainder being water; preferably, the mass content of isopropylamine chain dodecylbenzene sulfonate is 60wt% to 90wt%. The stabilizer is preferably P-1059, such as the commercially available AkzoNobel brand dispersant Witconate P-1059.

[0017] Further, in step (2), the soluble copper salt solution and the precipitant solution obtained in step (1) are added to the reactor in parallel flow, and the pH value of the system is controlled to be 6.5 to 7.5.

[0018] Furthermore, in step (2), the reaction conditions are: temperature of 15 to 70°C and time of 1 to 30 minutes.

[0019] Further, in step (3), the specific method of filtration is as follows: filtration is performed using a microporous filter membrane. The pore size of the microporous filter membrane is 0.2–2 μm, preferably 0.22–0.45 μm.

[0020] Further, in step (3), the first washing is a rinse using cold water. The temperature of the cold water is 0–8°C. The rinsing can be performed in a funnel. The first washing is performed 1–2 times.

[0021] Further, in step (4), the solvent is isopropanol. The amount of solvent used is not particularly limited; generally, it is sufficient to completely impregnate the material being treated. The freezing conditions are: a temperature of -16°C to -20°C, and a time of 5 to 8 hours.

[0022] Further, in step (5), the second washing is performed by rinsing with anhydrous ethanol. The second washing is performed 2 to 4 times. The second washing can be carried out at 10 to 25°C.

[0023] Further, in step (5), the third wash is a rinse using cold water. The temperature of the cold water is 0–8°C. The rinsing can be performed in a funnel. The third wash is performed 2–4 times.

[0024] Furthermore, in step (5), the fourth wash is performed using anhydrous ethanol, and the fourth wash is repeated 2 to 4 times. The fourth wash can be performed at 10 to 25°C.

[0025] Further, in step (5), the freeze-drying conditions are: a temperature of -40°C to -50°C and a time of 12 to 72 hours, preferably 36 to 72 hours.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] This invention is the first to propose a method for preparing amorphous basic copper carbonate products. Through the coordinated operation of various steps, especially the use of specific stabilizers and appropriate low-temperature washing and freeze-drying conditions, the crystal transformation of amorphous basic copper carbonate during the preparation process can be effectively avoided. Moreover, the method of this invention is simple and easy to operate, and does not require expensive instruments. Attached Figure Description

[0028] Figure 1 The XRD patterns are of basic copper carbonate and the samples obtained in Example 1, Comparative Example 1, and Comparative Example 2.

[0029] Figure 2 A photograph of the actual sample obtained in Example 1;

[0030] Figure 3 A photograph of the actual sample obtained in Comparative Example 1;

[0031] Figure 4 This is a photograph of the actual sample obtained in Comparative Example 2. Detailed Implementation

[0032] The present invention will be further illustrated by the following embodiments, but these embodiments do not limit the scope of the invention.

[0033] In this invention, the XRD test instrument used is a Rigaku Corporation D / MAX2500 X-ray diffractometer.

[0034] In this invention, the P-1059 used is all AkzoNobel brand commercial dispersant Witconate P-1059, of which the mass content of isopropylamine chain dodecylbenzene sulfonate is 90 wt%, and the remainder is water.

[0035] Example 1

[0036] (1) Weigh Cu(NO3)2·3H2O solid and dissolve it in deionized water to prepare 100 mL of soluble copper salt solution with a concentration of 0.2 mol / L; weigh anhydrous Na2CO3 solid and dissolve it in deionized water to prepare 100 mL of precipitant solution with a concentration of 0.2 mol / L.

[0037] (2) Add 50 mL of bottom water to the beaker, add 0.5 g of P-1059 while stirring, add the soluble copper salt solution and precipitant solution obtained in step (1) to the beaker in parallel, control the pH value of the system to 7.0, stir and mix at room temperature (20℃) for 15 min to obtain a slurry;

[0038] (3) The slurry obtained in step (2) was immediately filtered with a 0.22 μm microporous membrane under heat preservation. The precipitate was rinsed once in a funnel with 100 mL of cold water at 0 °C.

[0039] (4) Transfer the material obtained in step (3) into 30 mL of isopropanol and freeze at -18°C for 5 h in a freezer.

[0040] (5) The material from step (4) was rinsed three times with 100 mL of anhydrous ethanol at room temperature (20°C); then rinsed three times with 100 mL of cold water at 0°C; finally, it was rinsed three times with 100 mL of anhydrous ethanol at room temperature (20°C) and dried in a freeze dryer at -45°C for 48 hours to obtain the final sample.

[0041] The XRD pattern of the sample is shown below. Figure 1 See actual product photos. Figure 2 , among which, from Figure 1 It can be seen that no XRD characteristic peaks appeared in the sample. Figure 2 The sample is light blue, indicating that it is amorphous basic copper carbonate.

[0042] Example 2

[0043] (1) Weigh CuSO4·5H2O solid and dissolve it in deionized water to prepare 100 mL of soluble copper salt solution with a concentration of 2 mol / L; weigh NaHCO3 solid and dissolve it in deionized water to prepare 100 mL of precipitant solution with a concentration of 2 mol / L.

[0044] (2) Add 50 mL of bottom water to the beaker, add 0.7 g of P-1059 while stirring, and add the soluble copper salt solution and precipitant solution obtained in step (1) to the beaker in parallel flow. Control the pH value of the system to 7.0, stir and mix at 15℃ for 2 min to obtain a slurry.

[0045] (3) The slurry obtained in step (2) was immediately filtered with a 0.22 μm microporous membrane under heat preservation. The precipitate was rinsed once in a funnel with 100 mL of 0℃ cold water.

[0046] (4) Transfer the material obtained in step (3) into 50 mL of isopropanol and freeze at -18°C for 8 hours in a freezer.

[0047] (5) The material from step (4) was rinsed three times with 100 mL of anhydrous ethanol at room temperature (20°C), and then rinsed three times with 100 mL of cold water at 0°C. Finally, it was rinsed three times with 100 mL of anhydrous ethanol at room temperature (20°C) and dried in a freeze dryer at -40°C for 72 hours. The final sample was obtained. The color and XRD of this sample were similar to those of Example 1, indicating that it was amorphous basic copper carbonate.

[0048] Example 3

[0049] (1) Weigh Cu(NO3)2·3H2O solid and dissolve it in deionized water to prepare 100 mL of soluble copper salt solution with a concentration of 0.2 mol / L; weigh anhydrous Na2CO3 solid and dissolve it in deionized water to prepare 100 mL of precipitant solution with a concentration of 0.2 mol / L.

[0050] (2) Add 50 mL of bottom water to the beaker, add 0.5 g of P-1059 while stirring, add the soluble copper salt solution and precipitant solution obtained in step (1) to the beaker in parallel, control the pH value of the system to 7.0, stir and mix at a constant temperature of 50℃ for 2 min to obtain a slurry.

[0051] (3) The slurry obtained in step (2) was immediately filtered with a 0.45 μm microporous membrane under heat preservation. The precipitate was rinsed once in a funnel with 150 mL of 4℃ cold water.

[0052] (4) Transfer the material obtained in step (3) into 30 mL of isopropanol and freeze at -20°C for 5 h in a freezer.

[0053] (5) The material from step (4) was rinsed four times with 150 mL of anhydrous ethanol at room temperature (15°C); then rinsed twice with 150 mL of cold water at 4°C; finally, it was rinsed twice with 150 mL of anhydrous ethanol at room temperature (15°C) and dried in a freeze dryer at -45°C for 16 hours to obtain the final sample. The color and XRD of this sample were similar to those of Example 1, indicating that it was amorphous basic copper carbonate.

[0054] Example 4

[0055] (1) Weigh Cu(NO3)2·3H2O solid and dissolve it in deionized water to prepare 100 mL of soluble copper salt solution with a concentration of 0.2 mol / L; weigh anhydrous Na2CO3 solid and dissolve it in deionized water to prepare 100 mL of precipitant solution with a concentration of 0.2 mol / L.

[0056] (2) Add 50 mL of bottom water to the beaker, and add 0.5 g of P-1059 while stirring. Add the soluble copper salt solution and precipitant solution obtained in step (1) to the beaker in parallel flow, control the pH value of the system to 7.2, and stir and mix at a constant temperature of 35℃ for 20 min to obtain a slurry.

[0057] (3) The slurry obtained in step (2) was immediately filtered with a 0.22 μm microporous membrane under heat preservation. The precipitate was rinsed once in a funnel with 100 mL of 4℃ cold water.

[0058] (4) Transfer the material obtained in step (3) into 30 mL of isopropanol and freeze at -16°C for 8 hours in a freezer.

[0059] (5) The material from step (4) was rinsed three times with 100 mL of anhydrous ethanol at room temperature (20°C); then rinsed three times with 100 mL of cold water at 4°C; finally, it was rinsed three times with 100 mL of anhydrous ethanol at room temperature (20°C) and dried in a freeze dryer at -40°C for 24 hours to obtain the final sample. The color and XRD of this sample were similar to those of Example 1, indicating that it was amorphous basic copper carbonate.

[0060] Example 5

[0061] (1) Weigh Cu(NO3)2·3H2O solid and dissolve it in deionized water to prepare 100 mL of soluble copper salt solution with a concentration of 0.5 mol / L; weigh anhydrous Na2CO3 solid and dissolve it in deionized water to prepare 100 mL of precipitant solution with a concentration of 0.5 mol / L.

[0062] (2) Add 50 mL of bottom water to the beaker, add 0.5 g of P-1059 while stirring, add the soluble copper salt solution and precipitant solution obtained in step (1) to the beaker in parallel, control the pH value of the system to 6.5, stir and mix at a constant temperature of 65℃ for 2 min to obtain a slurry.

[0063] (3) The slurry obtained in step (2) was immediately filtered with a 0.22 μm microporous membrane under heat preservation. The precipitate was rinsed once in a funnel with 150 mL of 4℃ cold water.

[0064] (4) Transfer the material obtained in step (3) into 35 mL of isopropanol and freeze at -18°C for 6 h in a freezer.

[0065] (5) The material from step (4) was rinsed three times with 150 mL of anhydrous ethanol at 15°C; then rinsed four times with 150 mL of cold water at 4°C; finally, it was rinsed three times with 150 mL of anhydrous ethanol at 15°C and dried in a freeze dryer at -40°C for 36 hours to obtain the final sample. The color and XRD of this sample were similar to those of Example 1, indicating that it was amorphous basic copper carbonate.

[0066] Comparative Example 1

[0067] (1) Weigh Cu(NO3)2·3H2O solid and dissolve it in deionized water to prepare 100 mL of soluble copper salt solution with a concentration of 0.2 mol / L; weigh anhydrous Na2CO3 solid and dissolve it in deionized water to prepare 100 mL of precipitant solution with a concentration of 0.2 mol / L.

[0068] (2) Add 50 mL of bottom water to the beaker, and add the soluble copper salt solution and precipitant solution obtained in step (1) to the beaker in parallel. Control the pH value of the system to 7.0, stir and mix at room temperature (20℃) for 15 min to obtain a slurry.

[0069] (3) The slurry obtained in step (2) was immediately filtered with a 0.22 μm microporous membrane under heat preservation. The precipitate was rinsed once in a funnel with 100 mL of cold water at 0 °C.

[0070] (4) Transfer the material obtained in step (3) into 30 mL of isopropanol and freeze at -18°C for 5 h in a freezer.

[0071] (5) The material from step (4) was rinsed three times with 100 mL of anhydrous ethanol at room temperature (20°C); then rinsed three times with 100 mL of cold water at 0°C; finally, it was rinsed three times with 100 mL of anhydrous ethanol at room temperature (20°C) and dried in a freeze dryer at -45°C for 48 hours to obtain the final sample.

[0072] The XRD pattern of the sample is shown below. Figure 1 See actual product photos. Figure 3 , among which, from Figure 1 It can be seen that the sample of Comparative Example 1 showed obvious XRD characteristic peaks of basic copper carbonate crystals, indicating that the sample had undergone crystal transformation. Figure 3 The intermediate sample is green, which is consistent with the color of conventional basic copper carbonate.

[0073] Comparative Example 2

[0074] (1) Weigh Cu(NO3)2·3H2O solid and dissolve it in deionized water to prepare 100 mL of soluble copper salt solution with a concentration of 0.2 mol / L; weigh anhydrous Na2CO3 solid and dissolve it in deionized water to prepare 100 mL of precipitant solution with a concentration of 0.2 mol / L.

[0075] (2) Add 50 mL of bottom water to the beaker, add 0.5 g of P-1059 while stirring, add the soluble copper salt solution and precipitant solution obtained in step (1) to the beaker in parallel, control the pH value of the system to 7.0, stir and mix at room temperature (20℃) for 15 min to obtain a slurry;

[0076] (3) The slurry obtained in step (2) was immediately filtered with a 0.22 μm microporous membrane under heat preservation. The precipitate was rinsed once in a funnel with 100 mL of cold water at 0 °C.

[0077] (4) Transfer the material obtained in step (3) into 30 mL of isopropanol and freeze at -18°C for 5 h in a freezer.

[0078] (5) Rinse the material from step (4) three times with 100 mL of anhydrous ethanol at room temperature (20°C); then rinse three times with 100 mL of cold water at 0°C; finally rinse three times with 100 mL of anhydrous ethanol at room temperature (20°C) and dry in an oven at 45°C for 72 hours. The final sample is obtained.

[0079] The XRD pattern of the sample is shown below. Figure 1 See actual product photos. Figure 4 , among which, from Figure 1 It can be seen that the sample of Comparative Example 2 showed obvious XRD characteristic peaks of basic copper carbonate crystals, indicating that the sample had undergone crystal transformation. Figure 4 The color of the comparative example 2 sample is green, which is consistent with the color of conventional basic copper carbonate.

[0080] Comparative Example 3

[0081] (1) Weigh Cu(NO3)2·3H2O solid and dissolve it in deionized water to prepare 100 mL of soluble copper salt solution with a concentration of 0.2 mol / L; weigh anhydrous Na2CO3 solid and dissolve it in deionized water to prepare 100 mL of precipitant solution with a concentration of 0.2 mol / L.

[0082] (2) Add 50 mL of bottom water to the beaker, add 0.5 g of P-1059 while stirring, add the soluble copper salt solution and precipitant solution obtained in step (1) to the beaker in parallel, control the pH value of the system to 7.0, stir and mix at room temperature (20℃) for 15 min to obtain a slurry;

[0083] (3) Immediately filter the slurry obtained in step (2) using a 0.22 μm microporous membrane under heat preservation, and rinse once with 100 mL of deionized water at room temperature (20 °C).

[0084] (4) The material obtained in step (3) was rinsed three times with 100 mL of anhydrous ethanol at room temperature (20°C), and then rinsed three times with 100 mL of deionized water. Finally, it was rinsed three times with 100 mL of anhydrous ethanol at room temperature (20°C) and dried in a freeze dryer at -45°C for 48 h to obtain the final sample. The color and XRD of this sample were similar to those of Comparative Example 2, and it was a basic copper carbonate crystal.

Claims

1. A method for preparing amorphous basic copper carbonate, characterized in that, include: (1) Prepare soluble copper salt solution and precipitant solution separately; (2) Add bottom water and stabilizer to the reactor, and add the soluble copper salt solution and precipitant solution obtained in step (1) to the reactor in parallel flow. React under stirring to obtain a slurry; the stabilizer is a solution containing isopropylamine chain dodecylbenzene sulfonate. (3) The slurry obtained in step (2) is filtered and washed for the first time; (4) Add the material obtained in step (3) to the solvent and freeze; (5) The material from step (4) is washed in sequence, followed by a second, third and fourth washes. The washed material is then freeze-dried to obtain amorphous basic copper carbonate.

2. The method according to claim 1, characterized in that, In step (1), the soluble copper salt solution is at least one of Cu(NO3)2 solution, CuSO4 solution, and CuCl2 solution; the concentration of the soluble copper salt solution is 0.1 to 5 mol / L.

3. The method according to claim 1, characterized in that, In step (1), the precipitant solution is at least one of Na2CO3 solution, NaOH solution, and NaHCO3 solution; the concentration of the precipitant solution is 0.1 to 5 mol / L.

4. The method according to claim 1, characterized in that, In step (2), the amount of bottom water added is 5% to 20% of the total volume of solution finally added to the reactor.

5. The method according to claim 1, characterized in that, In step (2), the amount of stabilizer added is 0.5wt% to 1.5wt% of the mass of the bottom water.

6. The method according to claim 1, characterized in that, In step (2), based on the mass of the stabilizer, the mass content of isopropylamine chain dodecylbenzene sulfonate is 10wt% to 90wt%, with the remainder being water; preferably, the mass content of isopropylamine chain dodecylbenzene sulfonate is 60wt% to 90wt%.

7. The method according to claim 1 or 6, characterized in that, The stabilizer is P-1059.

8. The method according to claim 1, characterized in that, In step (2), the soluble copper salt solution and the precipitant solution obtained in step (1) are added to the reactor in parallel flow, and the pH value of the system is controlled to be 6.5 to 7.

5.

9. The method according to claim 1, characterized in that, In step (2), the reaction conditions are: temperature of 15 to 70°C and time of 1 to 30 minutes.

10. The method according to claim 1, characterized in that, In step (3), the specific method of filtration is as follows: filtration is performed using a microporous filter membrane, wherein the pore size of the microporous filter membrane is 0.20 to 2.0 μm, preferably 0.22 to 0.45 μm.

11. The method according to claim 1, characterized in that, In step (3), the first washing is a rinse with cold water, wherein the temperature of the cold water is 0 to 8°C; the first washing is performed 1 to 2 times.

12. The method according to claim 1, characterized in that, In step (4), the solvent is isopropanol.

13. The method according to claim 1, characterized in that, In step (4), the freezing conditions are: temperature of -16°C to -20°C, and time of 5 to 8 hours.

14. The method according to claim 1, characterized in that, In step (5), the second washing is performed by rinsing with anhydrous ethanol; the second washing is performed 2 to 4 times; the second washing is carried out at 10 to 25°C.

15. The method according to claim 1, characterized in that, In step (5), the third washing is a rinse with cold water; wherein the temperature of the cold water is 0 to 8°C; and the third washing is performed 2 to 4 times.

16. The method according to claim 1, characterized in that, In step (5), the fourth wash is a rinse with anhydrous ethanol, and the fourth wash is performed 2 to 4 times; the fourth wash is performed at 10 to 25°C.

17. The method according to claim 1, characterized in that, In step (5), the freeze-drying conditions are: temperature of -40°C to -50°C, time of 12 to 72 hours, preferably 36 to 72 hours.

Citation Information

Patent Citations

  • Preparation method of basic cupric carbonate

    CN111132932A